Doi-Peliti field theory of free active ornstein-uhlenbeck particles - Bothe,M; Pruessner,G (Physical Review E: Statistical, Nonlinear, and Soft Matter Physics, 2021)
We derive a Doi-Peliti field theory for free active Ornstein-Uhlenbeck particles, or, equivalently, free inertial Brownian particles, and present a way to diagonalize the quadratic part of the action and calculate the propagator. Unlike previous coarse-grained approaches this formulation correctly tracks particle identity and yet can easily be expanded to include potentials and arbitrary reactions.